O protagonismo da gestão educacional na efetivação da inclusão de estudantes surdos nos institutos federais de educação, ciência e tecnologia - Krebs, Josiane Roberta (Universidade do Vale do Rio dos Sinos, 2017)
The purpose of this study was to analyze how management processes related to the accessibility and inclusion of deaf students are structured in the Instituto Federal Educação, Ciência e Tecnologia do Rio Grande do Sul (Federal Institute of Education, Science and Technology of Rio Grande do Sul - IFRS) and the Instituto Federal Educação, Ciência e Tecnologia de Santa Catarina (Federal Institute of Education, Science and Technology of Santa Catarina - IFSC), considering the factors of access, permanence and success of these students, so that with the results of the analysis could be proposed improvements in order to enable the effective accessibility and inclusion of deaf students, extending the possibility for all Federal Institutes of Education, Science and Technology (IFs). The methodology adopted was the study of case, considering multiple cases, and the data collection was divided into two stages. In the first stage, the documentary analysis was carried out, considering IFRS and IFSC institutional legislation and normative documents related to accessibility and inclusion. In the second stage, deaf students, translators / interpreters of Libras, teachers and managers, selected in a joint way between the two institutions were interviewed, in a total of fourteen participants. The data obtained were systematized, allowing content analysis and mapping of management processes. The main results indicate the commitment of the IFs to make possible the accessibility and inclusion of deaf students, being identified in the process mapping actions aimed at institutional disclosure, admission and permanence of deaf students, however, they are still isolated and punctual actions. Regarding the needs of deaf students was realized the importance of recognizing and accepting their cultural and linguistic differences, which are mainly summarized in the forms of communication and in the use of Libras. The study concludes that in order to make possible the accessibility and inclusion of deaf students, the management processes should be related to the stages of institutionalization of guidelines for accessibility and inclusion, access, permanence, success and inclusion of the deaf egress in the world Work and society, all of which are based on the principles of access, respect, formation and social commitment of IFs.
Keywords: Acessibilidade e inclusão; Surdos; Gestão educacional; Processos; Institutos federais; Accessibility and inclusion; Deaf; Educational management; Processes; Federal institutes; ACCNPQ::Ciências Humanas::Educação